Effect offarmyard manure, phosphorus and zinc levels on growth, yield, quality and economics of pearl millet (Pennisetum glauculn) - JAKHAR, S R; SINGH, M; BALAI, C M (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted at Agronomy Farm, SKN College of Agriculture, Johner during rainy season of 2000 and 2001 to study the influence of graded levels of farm yard manure (0,5 and 10 tonneslha), phosphorus (0,8.73, 17.47 and 26.20 kg P/ha) and zinc (0, 5 and 10 kg Zn/ha) on growth, yield, quality and economics of pearl millet (Pennisetun1 glaucul1z) production. Application of 5 tonnes farm yard manure/ha and 17.47 kg P/ha significantly enhanced plant height, yield attributes (ear head length and test weight), grain yield, stover yield, protein content of grain and net return. Increasing levels of zinc significantly enhanced the plant height, grain yield and net return up to 10 kg Zn/ha, whereas significant increase in stover yield, protein content of grain only up to 5 kg Zn/ha of pearl millet.